Lyme disease, An Emerging Infection in Nepal: A Case Report - Khatri, Prabin; Sah, Chandra Mohan; Piryani, Rano Mal; Chaudhary, Shatdal; Dhakal, Puspa Raj; Shahi, Anita; Karki, Manoj; Shah, Pooja; Sapkota, Suman; Neupane, Aryan (Journal of Universal College of Medical Sciences, 2020)
ABSTRACT Lyme disease, an infectious multisystemic disease is caused by "Borrelia burgdorferi". It is a spirochete transmitted by the Ixodes tick. Until today, only one case has been reported from Nepal. Here we report case of a 50-year female from Gulmi, who presented with a history of fever, multiple joint pain, tiredness, tingling sensation, and a painful brownish raised lesion over the neck and anterior chest. The clinical diagnosis was confirmed by histological findings typical of erythema chronicum migrans and by serology. The patient was treated successfully with doxycycline. This is the second case report of Lyme disease from Nepal and the first documented case who presented with typical erythema chronicum migrans. We suspect that Lyme disease might not have been considered in the differential diagnosis of fever with rash and joint pain in Nepal and suggest that it is to be kept as a differential in the given scenario.